A case report of an endometriosis cyst at cesarean scar defect and review of literature - Ruibo Xu; Xinlei Xia; Ying Liu; Xiaoli Du; Zengfang Hao; Lili Wang; Jiexian Du (BMC, 2022)
Abstract Background Cesarean scar defect (CSD) presents as a cystic defect that connects the uterine cavity at the site of the previous cesarean section (CS). Endometriosis refers to the discovery of endometrial glands and stroma outside the uterine cavity. Cases of endometriosis cysts at CSD have not been reported. Case presentation In this article, we will present a patient with an endometriosis cyst at CSD with symptoms of a prolonged menstrual cycle, periods without cyclic abdominal pain, and a history of cesarean delivery. The gynecologic ultrasound showed a CSD and a mixed mass in the right front of the uterus. After about 1 month, the tumor grew from a diameter of 4.75 cm to 8.06 × 6.23 × 3.66 cm. The patient eventually had an operation, which revealed a mass protruding from the incision in the anterior uterine wall, which was attached to the anterior uterine wall by a thin tip with a smooth surface. Intraoperative rapid cytopathology suggested that endometrial glands were seen within the smooth muscle tissue, similar to endometriosis. Subsequently, the patient underwent resection of the endometriotic cyst. Final paraffin pathology showed smooth muscle with visible endometrial glands and old hemorrhage, and a one-year follow-up showed no recurrence of endometriosis cysts at CSD. Conclusions Endometriosis cysts at CSD are very rare. The clinical symptoms may be less obvious, and the diagnosis relies mainly on the patient's previous surgical history and imaging. A finding of a pelvic mass in the location of the CSD, with or without symptoms of menstrual changes and intermittent abdominal pain, should be considered an endometriotic cyst at CSD. Surgical treatment is a good choice for this disease. Further studies are needed regarding the etiological mechanism of this case and why the mass enlarged rapidly in one mouth.